THE EFFECT OF CAPITAL STRUCTURE AND PROFITABILITY TO FIRM VALUE - Nainggolan, Kelian Stephen Karuyan; Hutabarat, Francis (Universitas Indo Global Mandiri Palembang, 2023)
Abstract The purpose of the research is to obtain empirical evidence about the impact of growth, capital structure and profitability to firm value. The sample in this research is Index BUMN20 company which listed in Indonesia Stock Exchange during the period of 2019 –2022. The source of the data of this research was conducted from annual report and sustainability report. This research is using quantitative approach with multiple linear regression analysis method. The result in this research is suggested to find the effect of capital structure and profitability on firm value.